DI BALIK EKSISTENSI LOKALISASI DANAU TEMPE: ELIT POLITIK DAN SHADOW STATE - Kusuma Wicitra, Made Widyarini; Putra Erawan, I Ketut; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2021)
The sustainability of the localization business in the Sanur area is an interesting thing in this study by explaining the power of the political elite in the existence of the localization business